A Study on the Flow Field and the Structure of Fire Plumes in the Coupling Process of the Water Mist and the Jet Fire of Diesel Fuel. (2018) - Wang, Liang; Su, Shi-chuan; Wei, Cheng-yin; Chen, Chang-yun
Abstract: The diesel fuel is an important fire source in a ship's fire. Because of the diesel and the water is undissolved, so some combustion characteristics will be existed in the coupling process of the water mist and the diesel fire. Based on this problem, the flow field and the structure of diesel fire plumes are studied in this paper. By using the Smagorinsky model and the mixture fraction combustion model, the three-dimensional governing equations of fire plumes are built. The properties of the water mist are described by the cumulative volume fraction, the droplet transport equation, and the model of suppress fire. The result shows that the non-axial symmetry structure of fire plume and the entrainment phenomenon is formed by the water mist in the early stage of fire spread, and it is strengthen the combustion of flame. But in the later stage of fire spread, the fire can be suppressed effectively, then the flow field is become relative stability. In addition, the high value of water vapour concentration (greater than 0.1) and the greater of temperature gradient (350 K/m) are located in the height range of 0.9H to H in the compartment (H is the height of compartment). However, for the situation of no water mist, the vortex flow in fire field is more complexity during the whole fire developing process. Computational results have important significance for the water mist to be used in the fire extinguishing system of the ship engineer room.